2017
DOI: 10.1016/j.cjca.2017.08.022
|View full text |Cite
|
Sign up to set email alerts
|

2017 Comprehensive Update of the Canadian Cardiovascular Society Guidelines for the Management of Heart Failure

Abstract: Since the inception of the Canadian Cardiovascular Society heart failure (HF) guidelines in 2006, much has changed in the care for patients with HF. Over the past decade, the HF Guidelines Committee has published regular updates. However, because of the major changes that have occurred, the Guidelines Committee believes that a comprehensive reassessment of the HF management recommendations is presently needed, with a view to producing a full and complete set of updated guidelines. The primary and secondary Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
529
0
42

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 573 publications
(575 citation statements)
references
References 655 publications
(633 reference statements)
4
529
0
42
Order By: Relevance
“…Notwithstanding skepticism in the hematological community about this "extensive" definition, IV iron supplementation with FCM in CHF patients was effective in ameliorating either iron stores or cardiac function [74]. Such results have been consistently replicated [75,124], so that most recent and authoritative guidelines suggest to systematically check for ID in CHF and IV iron treatment if ID is present [125][126][127]. Noteworthy, a sub-analysis of the seminal FAIR-HF trial [74] focusing on anemic CHF patients showed consistent Hb increase after IV iron, implicitly validating the above mentioned "extensive" criteria for ID [128].…”
Section: Expanding Spectrum Of Clinical Use Of IV Ironmentioning
confidence: 99%
“…Notwithstanding skepticism in the hematological community about this "extensive" definition, IV iron supplementation with FCM in CHF patients was effective in ameliorating either iron stores or cardiac function [74]. Such results have been consistently replicated [75,124], so that most recent and authoritative guidelines suggest to systematically check for ID in CHF and IV iron treatment if ID is present [125][126][127]. Noteworthy, a sub-analysis of the seminal FAIR-HF trial [74] focusing on anemic CHF patients showed consistent Hb increase after IV iron, implicitly validating the above mentioned "extensive" criteria for ID [128].…”
Section: Expanding Spectrum Of Clinical Use Of IV Ironmentioning
confidence: 99%
“…İşlem sırasında verilen sistemik antikogulanlar nedeniyle sistemik kanama riski de vardır. [265] Fayda ve yararı işlemi yapan merkezin tecrübesine göre değişkenlik gösterir.…”
Section: Renal Replasman Tedavileri; Ultrafiltrasyon Diyalizunclassified
“…[266,267] Bu nedenle kılavuzlarda tüm diüretik stratejileri başarısız oldu ise dirençli konjesyonu olan hastalarda kısa süreli ve tekrarlayan ultrafiltrasyon uygulaması önerilmekte-dir. [4,17,265] Kalp yetersizliğinde ultrafiltrasyon'un etkinliğini daha iyi değerlendirmek için ileriki çalışmalarda göz önüne alınması gerekenleri şu şekilde özetleyebiliriz; -Hasta seçiminde renal fonksiyonları bozulmamış olanların da alınması -Renal disfonksiyonu tedavi etmek değil korumak amaçlanmalı -Yavaş ve daha uzun süreli sıvı çekilmeli -Laboratuvar değerlerinin değil klinik sonlanımlar hedeflenmeli -Uzun dönem (>90 gün) sonuçlara bakılmalı -Yan etkileri azaltmak için basit cihazların kullanılması ve daha iyi destek sağlanması.…”
Section: Renal Replasman Tedavileri; Ultrafiltrasyon Diyalizunclassified
“…[1][2][3] Assessment of appropriate use requires patient-level knowledge of indications, contraindications, and tolerability. [1][2][3] Assessment of appropriate use requires patient-level knowledge of indications, contraindications, and tolerability.…”
Section: Introductionmentioning
confidence: 99%